What is social innovation? The paradigm shift and its relationship with Social Work - Alonso Puelles, Andoni; Echeverría Ezponda, Javier (Cuadernos de Trabajo Social, 2016)
Innovation is a fundamental part of social work. In recent years there has been a shift in the innovation paradigm, making it easier to accept this relationship. National and supranational policies aimed at promoting innovation appear to be specifically guided by this idea. To be able to affirm this hypothesis, it is necessary to review the perception that social workers have of their duties. It is also useful to examine particular cases that show how such social innovation arises.
Keywords: social innovation; paradigm shift; policies; Social Work